How spatial variation in areal extent and configuration of labile vegetation states affect the riparian bird community in Arctic Tundra - Henden, John-André; Yoccoz, Nigel; Ims, Rolf Anker; Langeland, Knut (PLoS ONE, 2013)
The Arctic tundra is currently experiencing an unprecedented combination of climate change, change in grazing pressure by large herbivores and growing human activity. Thickets of tall shrubs represent a conspicuous vegetation state in northern and temperate ecosystems, where it serves important ecological functions, including habitat for wildlife. Thickets are however labile, as tall shrubs respond rapidly to both abiotic and biotic environmental drivers. Our aim was to assess how large-scale spatial variation in willow thicket areal extent, configuration and habitat structure affected bird abundance, occupancy rates and species richness so as to provide an empirical basis for predicting the outcome of environmental change for riparian tundra bird communities. Based on a 4-year count data series, obtained through a large-scale study design in low arctic tundra in northern Norway, statistical hierarchical community models were deployed to assess relations between habitat configuration and bird species occupancy and community richness. We found that species abundance, occupancy and richness were greatly affected by willow areal extent and configuration, habitat features likely to be affected by intense ungulate browsing as well as climate warming. In sum, total species richness was maximized in large and tall willow patches of small to intermediate degree of fragmentation. These community effects were mainly driven by responses in the occupancy rates of species depending on tall willows for foraging and breeding, while species favouring other vegetation states were not affected. In light of the predicted climate driven willow shrub encroachment in riparian tundra habitats, our study predicts that many bird species would increase in abundance, and that the bird community as a whole could become enriched. Conversely, in tundra regions where overabundance of large herbivores leads to decreased areal extent, reduced height and increased fragmentation of willow thickets, bird community richness and species-specific ...